LEAD AND CADMIUN CONCENTRATION IN CATFISH (pangasius polyuronodon) OF THE LOWER PART OF SIAK RIVER - Husnah Husnah; Siswanta Kaban; Makri Makri (Research Center for Fisheries, 2010)
Siak River is one of four big rivers in Riau Province suffered from anthropogenic substances deriving from various human aciivities. The substances not only degrade the water quality but also influence aquatic organisms such as fish.